Industrial Policy as the Application of State Defense in the Era of Industrial Revolution 4.0 - Afrimadona, Afrimadona; Darmastuti , Shanti; Dwi Astuti, Wiwiek Rukmi (Department of International Relations Universitas Pertamina, 2020)
The rapid change in the information technology in the age of Industry 4.0 requires the government to produce an innovative and competitive industrial policy in order to push for an independent economic development. Amids the trend of industry 4.0, states are faced with a challenge of advancing national industries, such as the energy, food and beverage, automotive, electronics, chemical, textile and textile products industries. Using literature review over a number of cases of industrial policies in East Asia, this article argues that a national interest-based industrial policy can be seen as an implementation of the so-called state defense. This is because industrial policy is the product of the thoughts of individual policy-makers who are also the citizens to whom the obligation of state defense applies. Thus, rather than simply asking the general individual citizens to do state defense, the state, represented by the individual policy-makers should also think of their policy in terms of state defense, that is the defense of public interest.